Online Self-Disclosure in the Teman Curhat Bunda Community as An Effort to Maintain the Mental Health of Its Members - Yuniarti, Nisa Adisti; Rahmah, Ade; Utomo, Ardian Setio; Sagiyanto, Asriyani (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2025)
This study discusses the practice of online self-disclosure in the Teman Curhat Bunda community and how it contributes to maintaining the mental health of its members. This study aimed to understand how community members use online platforms to share their personal and emotional experiences and seek social support. The research methodology used was a qualitative approach with an ethnography method. The researcher conducted in-depth interviews with community members and conducted observations and content analysis of online interactions in the community. This study involved several Teman Curhat Bunda community members actively participating in various community activities. The results showed that online self-disclosure plays an essential role in helping community members maintain mental health. This practice allows community members to feel heard, to obtain emotional support, and to share relevant advice and experiences. In addition, online communication also facilitates the forming of more ISSN : 2614-1272; e-ISSN : 2720-9857 Online Self-Disclosure in the Teman Curhat Bunda Community as An Effort to Maintain the Mental Health of Its Members intimate and supportive relationships among community members. However, this study also identified several challenges in online self-disclosure, such as privacy risks and managing negative interactions.